Coupled Hydraulic-Thermal Modelling and Related Numerical Analysis on Rock Fractures. (23rd November 2020) - Pan, Yongjian; Wang, Huajun; Liu, Qiang
Abstract : Hydraulic-thermal coupling is a key problem in rock mass engineering, especially in the disposal of nuclear wastes in deep rock mass. To accurately describe the coupling action of rock mass when under the interaction of hydraulic stress and thermal, the hydraulic-thermal coupling solving methods were proposed in this paper; in addition, the corresponding hydraulic-thermal coupling program FRHT3D was complied. Consequently, the numerical simulation was performed, it can be concluded that the flow speed is faster when the coupling effect is considered at the unstable seepage stage, and the seepage coupling solution is larger than that of uncoupling. Furthermore, when the coupling effects are considered, the permeable water head solution is much larger than that of the uncoupling solution at the unstable seepage stage. The proposed hydraulic-thermal coupling solving methods and programs can be applied to rock mass engineering practice.